Marketing Factors Affecting Japanese Restaurant’s Decision Making in Soi Sukhumvit 55 in Bangkok Metropolitan Area - Panich, Tanompong (Rajapark Journal, 2022)
This research aimed to study influencing factors and consumer behavior. This research used mixed methodologies, between quantitative and qualitative methods. The sample consisted of 395 Japanese restaurant consumers and was selected by convenience sampling between September and November 2019. And the qualitative method was used with two-restaurant entrepreneur interviews or the owner perceptions. The instruments were the questionnaires and interviews. The research results were found as follows: 1. Females were more likely to have Japanese food than males because it was low in fat and nutritious for the body. The advice for the Japanese restaurant operators was to do promotions that could attract females and would be successful marketing; 2. The main objectives of consumer behavior, they usually consume Japanese food at least 1-2 times per month on weekdays and weekends, from 06.01 - 08.00 pm, and have taken service for around 1 or 2 hours with 3-4 friends/colleagues. The decision-making order from the menu, as well as the promotion. They mostly paid 1,001-2,000 Baht each time by credit card and arrived by private transport; and 3. The marketing factors found that the first factor was the product. And the second one was the price. As for Japanese food consumption values, consumers mainly wanted to try the new food menu. Entrepreneurs in the Japanese restaurant business need to adjust their strategies, offer exotic foods to meet the needs of consumers, and attract more consumers to Japanese restaurants.